Treatment of sharp mandibular alveolar process with hybrid prosthesis - Sukaedi Sukaedi; Eha Djulaeha (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Losing posterior teeth for a long time would occasionally lead to the sharpening of alveolar process. The removable partial denture usually have problems when used during mastication, because of the pressure on the mucosa under the alveolar ridge. Purpose: The purpose of this case report was to manage patients with sharp mandibular alveolar process by wearing hybrid prosthesis with extra coronal precision attachment retention and soft liner on the surface base beneath the removable partial denture. Case: A 76 years old woman visited the Prosthodontic Clinic Faculty of Dentistry Airlangga University. The patient had a long span bridge on the upper jaw and a free end acrylic removable partial denture on the lower jaw. She was having problems with mastication. The patient did not wear her lower denture because of the discomfort with it during mastication. Hence, she would like to replace it with a new removable partial denture. Case management: The patient was treated by wearing a hybrid prosthesis with extra coronal precision attachment on the lower jaw. Soft liner was applied on the surface of the removable partial denture. Hybrid prosthesis is a complex denture consisting of removable partial denture and fixed bridge. Conclusion: It concluded that after restoration, the patient had no problems with sharp alveolar process with her new denture, and she was able to masticate well.Latar belakang: Kehilangan geligi posterior dapat menimbulkan processus alveolaris tajam. Gigi tiruan sebagian lepasan mempunyai masalah selama pengunyahan karena adanya tekanan di mukosa di bawah alveolar ridge. Tujuan: Tujuan laporan kasus ini adalah untuk menjelaskan cara menangani pasien yang mempunyai prosesus alveolaris yang tajam di rahang bawah dengan dibuatkan protesis hybrid dengan daya tahan extra coronal precision attachment dan soft liner di permukaan bawah basis gigi tiruan sebagian lepasan. Kasus: Pasien wanita berumur 76 tahun datang di klinik Prostodosia Fakultas Kedokteran Gigi Universitas Airlangga. Pasien memakai gigi tiruan lekat rentang panjang di rahang atas dan gigi tiruan sebagian lepasan akrilik free end di rahang bawah, pasien mengalami masalah waktu mengunyah. Pasien tidak memakai gigitiruan lepasan rahang bawahnya karena tidak nyaman dipakai, dan pasien menginginkan pembuatan gigi tiruan lepasan rahang bawah yang baru. Tatalaksana kasus: Pada pasien ini dilakukan pembuatan Hybrid Prosthesis dengan daya tahan berupa extra coronal attachment di rahang bawah dan penggunaan bahan pelapis lunak yang diaplikasikan pada basis gigi tiruan lepasan nya. Hybrid prosthesis adalah gigi tiruan himpunan yang terdiri dari gigi tiruan lepasan dan gigi tiruan lekat. Kesimpulan: Hasil perawatan menunjukkan setelah mengganti gigi tiruan dengan gigi tiruan sebagian lepasan yang baru, pasien tidak mempunyai masalah dengan gigi tiruan yang baru akibat processus alveolaris yang tajam dan pasien dapat mengunyah dengan baik.